Конек-горбунок: сказки / Петр Ершов - Ершов Петр Павлович (Любимые сказки малышам, 2012)
Экземпляры: ДБ (20160516) / Инвентарный номер: 47982 / Цена: 159.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Е 80 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6